Hadith #2584 - Sahih al-Bukhari - Umm Kulthum bint 'Uqba (Sahih al-Bukhari)
That she heard Allah’s Messenger (ﷺ) saying, “He who makes peace between the people by inventing good information or saying good things, is not a liar.”
Grade: Sahih